Trajectories of Sugar Consumption and Dental Caries in Early Childhood. (June 2022) - Echeverria, M.S.; Schuch, H.S.; Cenci, M.S.; Motta, J.V.S.; Bertoldi, A.D.; Hallal, P.C.; Demarco, F.F.
This study verifies the association between the trajectory of sugar consumption and dental caries in the 2015 Pelotas Birth Cohort in Pelotas, Brazil. It was conducted with data from the follow-ups at 3, 12, 24, and 48 mo from the 2015 Birth Cohort, which included 4, 275 children born alive in hospitals in Pelotas. Data collection included standardized questionnaires for first caregivers applied by trained interviewers at all follow-ups. Exposure was the trajectory of sugar consumption from 3 to 48 mo (always low, always intermediate, increasing, and always high), obtained by group-based trajectory modeling. The outcome of this study was dental caries, obtained through clinical examination performed by calibrated dentists at 48 mo of age. Socioeconomic conditions and oral health instruction from a health professional during the first 4 y of life were included in the analysis as potential confounders. Prevalence ratios and their 95% confidence intervals were provided from generalized estimating equations with a log-Poisson with robust variance specification. In total, 3, 654 (91.1%) children participated in the survey at 48 mo, and 2, 806 children had complete data for the analyzes performed. Of these, 1, 012 (36.1%; 95% confidence interval [CI], 34.3–37.8) experienced caries, and 723 (25.8%; 95% CI, 24.2–27.4) had cavitated caries. Regarding cavitated caries, the prevalence was 1.48 times higher in the group with increasing sugar consumption than children with always low consumption. There is an association between the trajectory of sugar consumption and dental caries at 48 mo. Children with increasing and always high sugar consumption have the highest prevalence of caries.